Fish Consumption Pattern And Stunting In Toddlers In Gunungkidul Regency - Endang Pinta Utami; Evi Gravitiani; Izza Mafruhah (UNIVED Press, 2026)
This study aims to analyze the relationship between fish consumption patterns and stunting in toddlers in Gunungkidul Regency, Special Region of Yogyakarta. The study design uses a cross-sectional approach with cluster sampling techniques in two areas with the highest (Patuk 1) and lowest (Purwosari) prevalence of stunting. The total sample consisted of 309 toddlers aged 6–59 months, comprising 201 respondents in Patuk 1 and 108 in Purwosari. Independent variables included fish consumption frequency, portion size, fish type, and sociodemographic factors such as family income, maternal education, number of children, infectious diseases, sanitation, and area of residence. Data analysis was performed using logistic regression with Stata 14 software to identify factors significantly associated with stunting. The results showed that fish type was significantly associated with stunting, while frequency and portion size of consumption were not significantly associated. Other factors significantly associated with stunting were the mother's education level, number of children, and history of infectious diseases. Meanwhile, income, area of residence, and sanitation did not show a significant relationship. These findings confirm that the quality of fish consumed by toddlers has a greater impact on the risk of stunting than the frequency or portion size of consumption. Maternal education and child health are key protective factors. The results of this study are expected to form the basis for policies to increase consumption of nutritious fish and family nutrition education as strategies for preventing stunting based on local foods